Upconversion nanoparticles with a strong acid-resistant capping. Issue 14 (17th March 2016) - Recalde, Ileana; Estebanez, Nestor; Francés-Soriano, Laura; Liras, Marta; González-Béjar, María; Pérez-Prieto, Julia
Abstract : β-NaYF4 :Yb 3+, Er 3+ upconversion nanoparticles coated with a thin shell of a biocompatible copolymer comprising 2-hydroxyethylmethacrylate and 2-acrylamido-2-methyl-1-propanesulfonsulfonic acid are water-dispersible and remarkably resistant to strong acidic conditions. Abstract : Water-dispersible upconversion nanoparticles (β-NaYF4 :Yb 3+, Er 3+, UCNP) coated with a thin shell of a biocompatible copolymer comprising 2-hydroxyethylmethacrylate (HEMA) and 2-acrylamido-2-methyl-1-propanesulphonsulphonic acid (AMPS), which we will term COP, have been prepared by multidentate grafting. This capping is remarkably resistant to strong acidic conditions as low as pH 2. The additional functionality of the smart UCNP@COP nanosystem has been proved by its association to a well-known photosensitizer (namely, methylene blue, MB). The green-to-red emission ratio of the UC@COP@MB nanohybrid exhibits excellent linear dependence in the 7 to 2 pH range as a consequence of the release of the dye as the pH decreases.